Effects of filial piety belief on cyberbullying perpetration of Chinese university students - Wei Hua; Lu Lijun; Liu Meiting (FRONTIERS MEDIA SA, 2025)
Cyberbullying has become a worldwide phenomenon. Although the topic has drawn decent academic attention and many studies have been conducted on Chinese samples, variable interests in these studies have not captured the thinking and behavioral characteristics of Chinese people. Based on the dual filial piety model and self-determination theory, this study examined the effect of filial piety belief on cyberbullying perpetration and tested the mediation of relatedness need satisfaction. A total of 856 university students completed the questionnaires, including dual filial piety scale, relatedness need satisfaction scale and cyberbullying perpetration scale. The regression results found that reciprocal filial piety negatively predicted and authoritarian filial piety positively predicted cyberbullying perpetration. The SEM results showed that reciprocal filial piety and authoritarian filial piety impacted cyberbullying perpetration through the mediating effect of relatedness need satisfaction. Reciprocal filial piety was positively while authoritarian filial piety negatively correlated with relatedness need satisfaction and relatedness need satisfaction was negatively correlated with cyberbullying perpetration. The results provide a new position to understand the effect of family factors on cyberbullying perpetration by placing the topic within traditional Chinese family value.